The Evolution of Urban Australian Meat-Eating Practices - Khara, Tani; Riedy, Christopher; Ruby, Matthew B. (Frontiers in Sustainable Food Systems, 2021)
This qualitative study used social practice theory to explore how meat-eating practices are changing in contemporary urban Australia, drawing on a sample of Sydney residents aged 23–45 years. The research used an iterative study design and an inductive analysis approach. Semi-structured face-to-face in-depth interviews were the main mode of data collection, supplemented by observations in places such as markets and local neighborhoods. Research participants explained that the role of meat in their diet has changed in response to shifting conventions and social infrastructures. They have reduced consumption of red meat in favor of meats considered healthier or more ethical. Key factors driving the change include exposure to alternative eating practices brought about through changes in political policy and the advent of globalization. Changing discourses of masculinity and the move toward embracing more fluid representations of gender have, in turn, changed meanings in relation to the meat-eating man and a meat-heavy diet. Rising environmental and health consciousness, and concerns for animal welfare have also contributed to dietary changes. While several participants claimed to have increased their consumption of plant-based foods, meat still continues to maintain a significant presence within their diets. Many participants expressed interest in cutting back further on meat consumption and adopting more plant-based foods but they also identified several challenges—e.g., limited access to plant-based ingredients and recipes, negative meanings associated with vegetarian and vegan diets, and a lack of competence in relation to preparing and consuming appetizing meals using plant-based foods.